LA BIBLIOTECA BRITÁNICA (1807), UNA VENTANA ABIERTA A LA LITERATURA BRITÁNICA DE CARÁCTER INFANTIL Y JUVENIL - Begoña Lasa Álvarez (Cuadernos de Ilustración y Romanticismo)
In the second half of the eighteenth century and the beginning of the nineteenth century, due to new enlightened pedagogical theories, underlining the singularity of children and young people, literature for children and young adults became a rapidly developing genre, which was very lucrative for authors and editors. In this context the Biblioteca Británica was published in Spain in 1807. It was a collection of miscellaneous texts of British origin, whose aim was to instruct and entertain the youngest readers. Hence among its contents prominent authors who had written explicitly for this reading public could not be missing, including Letters from a Father to His Son (1794) by John Aikin, Evenings at Home (1792-1796) by the same Aikin and Anna Laetitia Barbauld and Rural Walks (1795) by Charlotte Smith.